Monitoring of Microbial Growth on Crude Oil Remediation using Processed Palm Fruit Fermented Waste Water and NKP Fertilizer - C. P Ukpaka; Adaobi Stephenie Nwosi-Anele (International Journal of Pollution: Prevention & Control, 2024)
The bacteria count was done to ascertain the microbial growth rate in each reactor and the research work demonstrates the integrity of fermented palm oil processed waste water obtained the available nutrients for the restoration of microbial activity in terms of growth as well as remediation of polluted clay soil environment for optimum utilization in terms of agricultural purposes. This study is based on the overview on the ability of the microbes to degradation the petroleum hydrocarbon and the effect of bio-stimulation on the growth of the bacteria and the fungi inoculated in each bio-reactor. This investigation demonstrates high microbial population of bacteria than fungi as well as revealed that physicochemical parameters played less role in terms of inhibiting characteristics. The growth of the bacteria was more significant in bio-stimulants of NPK fertilizer than the fermented palm oil processed waste water and this trend of characteristics was experienced for fungi as well.
Keywords: Microbial Growth; Monitoring; NKP fertilizer; Processed Palm Fruit Fermented Waste Water; crude oil; remediation